Challenges in management of pediatric life-threatening neck and chest trauma - Shilpa Sharma; Biplab Mishra; Amit Gupta; Kapil Dev Soni; Richa Aggarwal; Subodh Kumar (Wolters Kluwer Medknow Publications, 2018)
Introduction: Neck and thoracic trauma in children pose unforeseen challenges requiring variable management strategies. Here, we describe some unusual cases. Patients and Methods: Pediatric cases of unusual neck and thoracic trauma prospectively managed from April 2012 to March 2014 at a Level 1 trauma center were studied for management strategies, outcome, and follow-up. Results: Six children with a median age of 5.5 (range 2-10) years were managed. Mechanism of injury was road traffic accident, fall from height and other accidental injury in 2, 3 and 1 patient respectively. The presentation was respiratory distress and quadriplegia, exposed heart, penetrating injury in neck, dysphagia and dyspnea, and swelling over the chest wall in 1, 1, 1, 2 and 1 cases respectively. Injuries included lung laceration, open chest wall, vascular injury of the neck, tracheoesophageal fistula (2), and chest wall posttraumatic pyomyositis. One patient had a flare of miliary tuberculosis. Immediate management included chest wall repair; neck exploration and repair, esophagostomy, gastroesophageal stapling, and feeding jejunostomy (followed by gastric pull-up 8 months later). Chest tube insertion and total parenteral nutrition was required in one each. 2 and 4 patients required tracheostomy and mechanical ventilation. The patient with gastric pull-up developed a stricture of the esophagogastric anastomosis that was revised at 26-month follow-up. At follow-up of 40-61 months, five patients are well. One patient with penetrating neck injury suffered from blindness due to massive hemorrhage from the vascular injury in the neck and brain ischemia with only peripheral vision recovery. Conclusion: Successful management of neck and chest wall trauma requires timely appropriate decisions with a team effort.